ASEAN Halal Markets Analysis: Regulatory and Harmonization Challenges - Anggito Abimanyu; Ihda Arifin Faiz (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
This article examines important aspects of the halal market’s development, including halal food in seven advanced members of ASEAN countries. The qualitative method has been used by examining the main aspects of the regulation, a form of institutions, a SWOT analysis, a study of the impact of halal food regulations, and an analysis of ASEAN regulatory harmonization. Data on halal food regulations in ASEAN-7 countries were obtained from literature reviews, official documents, publications, interviews, and direct field observations. The study shows that halal regulations in ASEAN-7 generally are adequate for their purpose but reveal diversity in halal standards, institutional forms, internal and external environmental conditions, and their impacts. The implication shows that the ASEAN can potentially increase halal business and global halal trade. Although various efforts have been made, more synergistic cooperation is needed to develop harmonious halal trade regulations to increase economic, social, and consumer protection benefits for the ASEAN region. Originality/Value: This study investigates the existence of research gaps between empirical data and literature or theories concerning the trade in halal food products within the ASEAN region. The study on the harmonization of halal regulations in ASEAN and its relationship to trade flows has not been extensively conducted. It is hoped that this research will prove beneficial to both academic literature and the formulation of regional policies regarding the halal food trade among ASEAN countries.